The Role of Money Markets in Supporting Economic Growth And Business Capital Development - Aliano, Dio; Yulianti , Oni; Harwini, Dewi (Journal of Accounting and Management, 2024)
The money market has a crucial role in supporting economic growth and business capital development. By providing access to flexible and liquid sources of funds, money markets facilitate the investments needed to move the wheels of the economy. This article reviews the role of the money market in providing a fast and efficient source of funding for business actors, as well as its impact on overall economic growth. This analysis also discusses strategies that can be applied to increase the role of the money market in supporting business capital development and encouraging sustainable economic growth. In addition to supporting economic growth, the money market also plays an important role in the development of the capital market. Funds collected through money market instruments can be allocated to long-term investments through capital, such as stocks and bonds. It provides an important source of financing for companies looking to expand or develop new projects. Thus, sound and efficient market development is an important prerequisite for sustainable economic growth and inclusive capital market development. Further research is needed to understand more deeply the relationship between money markets, economic growth, and capital market development, as well as to formulate appropriate policies to strengthen the role of money markets in a dynamic economy.